Changes in voter behavior after an information signal: An experimental approach for Senegal - Christian H. C. A. Henning; Svetlana Petri; Daniel Diaz (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
Electoral competition is considered a control mechanism to guarantee a good performance of the government. However, in real life it often leads to a distorted policy implementation due to Government Capture and low Government Accountability. Therefore, the analysis of voter behavior is a key factor to understand government performance. More specifically, if voters choose more policy and retrospectively oriented, the government has greater incentives to implement efficient policies. In this sense, if voters have more information on politics, they are more likely to base their decision on policy issues. To assess changes in voter behavior, we carried out a political experiment, where information about the performance of the Senegalese government was delivered to a randomly selected group of voters. Then, based on election surveys data collected before and after the information signal, a probabilistic voter model with latent class using a panel data set was developed. Additionally, to evaluate changes in the relative importance of the three voting motives (policy, non-policy and retrospective), marginal effects and relative marginal effects were estimated. As expected, after the information signal, the relative importance of the policy and the retrospective components increased significantly. [...]
Keywords: Q18; C33; C35; C38; 330; probabilistic voter model; capture; accountability; agricultural policy; Senegal; Africa